Community Empowerment pada Program One Product One RW (OPOR) Di Kota Cimahi - Dewi Kurniasih; Apriani Puti Purfini (Jurnal Partisipatoris, 2024)
The aim of this research is to optimize the community empowerment model in Cimahi City through the One Product One RW (OPR) program after the Covid-19 pandemic. After the Covid-19 pandemic, Cimahi City became one of the cities in West Java Province that was affected by the Covid-19 pandemic. It is hoped that by re-implementing the OPOR program, the community will be more efficient and able to compete to create a prosperous Cimahi City. descriptive research method with a Mixed Method Sequential Explanatory model approach. The data collection and processing process will predominantly use a quantitative approach, supported by an explanation of the qualitative approach. The survey results will be processed using SPSS version 20 and Ms. Excel, while the interview data will be processed using NVivo12. The research results for the implementation quality of the One Product One RW (OPOR) Program in Cimahi City in 2023 are at an implementation quality score of 85. A score of 85 for the implementation quality of the OPOR Program indicates high implementation quality. It can be identified that the highest score is in the dimension of compatibility between the user group and the OPOR implementing organization with an implementation quality score of 86.8. , an indicator with 93% of respondents agreeing that the OPOR Program needs to be evaluated if it is to be continued and an indicator with 88.4% of respondents agreeing that the OPOR Program will be continued. This value shows that more respondents tend to want the OPOR program to be evaluated first before continuing. If the OPOR Program is to be continued, note that there needs to be a grouping of participants based on their business clusters, because the implementation of OPOR in 2023 is considered to combine fashion clusters with food, drink and craft value is unfair in terms of assessment weight.